AB0352 Significance of occult infections in inflammatory arthritis patients receiving biologic therapies in east london. (12th June 2018) - Alkoky, H.; Qadir, G.; Etomi, O.; Tahir, H.; Pakozdi, A.
Abstract : Background: Chronic hepatitis B virus (HBV) infection remains a significant global health problem. In high endemic areas like African and Asian countries, most infections occur from vertical transmission, whilst in western countries HBV is primarily acquired in adulthood. Either way, HBV can persist in infected hepatocytes lifelong, even if undetectable in the serum, allowing reactivation during immunosuppression. HBsAg carriers, those with detectable HBV viral load, or receiving concomitant corticosteroids are at greater risk. Most guidelines recommend screening for occult infections prior to starting biologic treatment including testing for HBV, HCV, HIV and TB infection. Objectives: This study was carried out to estimate the prevalence of occult infections, particularly chronic HBV, in an East London rheumatology population receiving biologic therapies, and to evaluate the rate of HBV reactivation after starting treatment. Methods: Inflammatory arthritis patients starting biologic therapies in Barts Health NHS Trust between August 2014 and August 2017 were identified from databases of Whipps Cross and Mile End Hospitals. Health records were reviewed focusing on HBV core antibody (HBcAb), HBV surface antigen (HBsAg), HBV DNA, HCV and HIV antibody status. Latent TB tests included IGRA and ELISpot assays. Results: 757 patients were included in the study. Of those, 51 (6.7%) were HBcAb positive, 6 patients (0.8%) were HBsAg positive and two patients had low level HBV viraemia with detectable DNA antibody at baseline. 61% (n=31) of HBcAb positive patients were female, whilst 39% (n=20) were male, with median age of 58 years (IQR, 43–65). The ethnic distribution was the following: 43% asian (n=22; Bangladeshi or Pakistani), 29% african or afro-Caribbean black (n=15), and 18% white caucasian (n=9). The underlying rheumatological conditions included rheumatoid arthritis (59%), ankylosing spondylitis (33%) and psoriatic arthritis (8%). Fifteen patients (29%) received concomitant prophylactic anti-viral therapies (lamivudine, entecavir or tenofovir). After commencing biologic therapies, no HBV reactivation was noted in the HBcAb positive cohort. Intermittent mild transaminitis were detected on monitoring blood tests in 22% (n=11). The rate of latent TB infection was 11.5%; HCV IgG was detected in three patients, whilst HIV infection was absent in our cohort. Conclusions: Approximately 50% of the patient population of Barts Health NHS Trust is coming from minority ethnic groups. Likely because of the diversity of the population, the prevalence of chronic HBV infection (HBsAg and HBcAb positives) in our East London rheumatology population receiving biologic therapies was higher than the national average (0.8% vs. 0.3%, respectively). No HBV reactivation was observed in the follow up period indicating that the risk of reactivation is relatively low. Nevertheless, for patients with evidence of previous infection (HBcAb positive) careful surveillance continues to be recommended. Disclosure of Interest: None declared